Pengajaran Bahasa Inggris Melalui Siaran Radio Komunitas Periode II - Ni Gusti Ayu Roselani (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Balai Budaya Minomartani (BBM) is a community center of Indonesian culture and arts, which has attracted a good number of domestic and foreign visitors. It is located in Minomartani village in Sleman, Yogyakarta. It has a community radio station on FM 107.9 Mhz. Although the radio is quite popular among the surrounding residents, it has a very limited program and none of them is for the young generation, especially children. This good potential has drawn the attention of the Community Engagement team of the English Department of the Faculty of Cultural Sciences of Universitas Gadjah Mada to provide some support in the form of English Lessons radio program. As the targets of the program are children in the community surrounding the center, the lessons make use of mostly fables to be the main teaching materials.